Structural and ferroelectric properties of 0.9PMN-0.1PT thin films. Issue 1 (14th July 2016) - Mietschke, M.; Engelhardt, S.; Fähler, S.; Molin, C.; Gebhardt, S.; Schultz, L.; Hühne, R.
ABSTRACT: Epitaxial films are a useful tool to study the interplay between the microstructure and the electrocaloric properties in order to optimize the performance of these materials. Therefore, epitaxial 0.9Pb(Mg1/3 Nb2/3 )O3 -0.1PbTiO3 (PMN-PT) films were grown by pulsed laser deposition on (001)-oriented single crystalline SrTiO3 (STO) substrates using an epitaxial La0.7 Sr0.3 CoO3 buffer as bottom electrode and additional Au top electrodes on the surface of the PMN-PT layer. The main goal of our study was to characterize the influence of the laser fluence on the structural properties. Our data show that pyrochlore-free PMN-PT films can be realized for low fluences. The relative permittivity and the polarization were determined as a function of temperature to verify the ferroelectric quality of our films.